A Mentally Ill Genius. Criticism of Reason in Daniel Kehlmann’s Works - MIZEROVÁ, Nikola (Anafora, 2023)
The criticism of reason (Vernunftkritik) is one of the crucial poetic intentions in Daniel Kehlmann’s work. In his texts pertaining to different genres, the author expresses the fragility of reason portrayed primarily through mentally reversible figures. However, he does not continue the long tradition of the genius in literature; he questions it and deals with this subject with an ironic undertone. This paper focuses on the three geniuses in Kehlmann’s prose and dramatic work, namely, on Alexander von Humboldt and Carl Friedrich Gauß in the novel Die Vermessung der Welt (Measuring the World, 2008), and on Kurt Gödel in the play Geister in Princeton (“Ghosts of Princeton,” 2019). While in the novel Kehlmann violates historical facts, challenges the rationality of the characters, confronts individual models of rationality, and introduces the topos of incomprehension, in his drama he achieves the criticism of reason by inserting a second fiction level which does not serve to tell the story, but to challenge the audience in terms of their knowledge and perception. The analysis of the novel and the play concludes the drama to be a medium having a more radical aesthetic effect than the novel. The play lets the audience experience the fragility of reason in depth when compared to the novel, the readers of which are allowed to reflect on the inadequacy of reason rationally and thus come up against its own limits.